(untitled) (Revista Brasileira Multidisciplinar, 2011)
This research aims to study the environmental perception of a group of residents of two neighborhoods surrounding the Botanical Garden City Park in Sinop-MT, revealing their relationship with the area as well as their involvement in proposing alternatives for the conservation of the Park. With this aim a study on the Botanical Garden Municipal Park was carried out, using the following procedures: documentary research in public agencies; site visits for description of the area and semi-structured interviews with a group of residents of two neighborhoods in the vicinity, Celeste Garden and the Botanical Garden. The presence of fauna, flora and springs that form Ribeirão Nilza within the park indicates the need for its conservation, and the residents consider the area important for the local micro weather, tourism, biodiversity conservation and also to develop researches, contributing significantly to the population’s quality of life. Taking into account the above considerations, it is important to consider a new scenario, which aims to mobilize social participation, propitiating the people the feeling of belonging to what they conceive as the environment, giving rise to a participatory management by means of Environmental Education.